NOP receptor pharmacological profile - A dynamic mass redistribution study. - Davide Malfacini; Katharina Simon; Claudio Trapella; Remo Guerrini; Nurulain T Zaveri; Evi Kostenis; Girolamo Calo' (PLoS ONE, 2018)
The Nociceptin/Orphanin FQ (N/OFQ) peptide NOP receptor is coupled to pertussis toxin (PTX)-sensitive G proteins (Gi/o) whose activation leads to the inhibition of both cAMP production and calcium channel activity, and to the stimulation of potassium currents. The label free dynamic mass redistribution (DMR) approach has been demonstrated useful for investigating the pharmacological profile of G protein-coupled receptors. Herein, we employ DMR technology to systematically characterize the pharmacology of a large panel of NOP receptor ligands. These are of peptide and non-peptide nature and display varying degrees of receptor efficacy, ranging from full agonism to pure antagonism. Using Chinese hamster ovary (CHO) cells expressing the human NOP receptor we provide rank orders of potency for full and partial agonists as well as apparent affinities for selective antagonists. We find the pharmacological profile of NOP receptor ligands to be similar but not identical to values reported in the literature using canonical assays for Gi/o-coupled receptors. Our data demonstrate that holistic label-free DMR detection can be successfully used to investigate the pharmacology of the NOP receptor and to characterize the cellular effects of novel NOP receptor ligands.